Pengaruh Model Contextual Teaching and Learning Terhadap Hasil Belajar IPA kelas V - Sukma Nuraini; Lili Yanti; Mertika (Universitas Muhammadiyah Kuningan, 2024)
This study aims to equip fifth grade students at SDN 26 Singkawang to: 1) recognize the comparison of student learning outcomes between classes that utilize the direct learning model and classes that utilize the Contextual Teaching and Learning (CTL) learning model in science subjects; and 2) identify the extent of the influence of the Contextual Teaching and Learning (CTL) model on the science learning skills of fifth grade students at SD Negeri 26 Singkawang. The method used is a quantitative test with a semi-exploratory plan. The posttest-only control design served as an exploratory configuration. This study only included fifth grade students at SDN 26 Singkawang, and the sample was taken using probability sampling. 1) There is a comparison of student learning outcomes between the class that practices the Contextual Teaching and Learning( CTL) model and the control class that uses the direct learning model, as evidenced by the results with = -436,74 > = 1,67 86. 2) Contextual Teaching and Learning (CTL) Learning Model influences science learning outcomes on topic 9 subtheme 1 learning 1 class V SDN 26 Singkawang with an Effect Size () trial of 2, 87 located in the upper class . The Contextual Teaching and Learning model has a significant influence on the science learning outcomes of fifth grade students at SDN 26 Singkawang, it can be concluded